2015
DOI: 10.1145/2754934
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Resilient Trust Management in Distributed Service Provision Networks

Abstract: Distributed service networks are popular platforms for service providers to offer services to consumers and for service consumers to acquire services from unknown parties. eBay and Amazon are two well-known examples of enabling and hosting such service networks to connect service providers to service consumers. Trust management is a critical component for scaling such distributed service networks to a large and growing number of participants. In this paper, we present ServiceTrust ++ , a feedback quality sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…We also compare the results against two state-of-the-art reputation systems, EigenTrust [30] and TNA-SL [28]. The reason for choosing these two systems is because they are the most known trust management systems and many recent proposed systems were based on them [31][32][33][34][35]; in addition, they are already implemented in the simulation tool [36] that we used in our evaluation. Based on the results, we found that our proposed system achieves a better performance in varying the number of CSPs and malicious CSPs in the system.…”
Section: Introductionmentioning
confidence: 99%
“…We also compare the results against two state-of-the-art reputation systems, EigenTrust [30] and TNA-SL [28]. The reason for choosing these two systems is because they are the most known trust management systems and many recent proposed systems were based on them [31][32][33][34][35]; in addition, they are already implemented in the simulation tool [36] that we used in our evaluation. Based on the results, we found that our proposed system achieves a better performance in varying the number of CSPs and malicious CSPs in the system.…”
Section: Introductionmentioning
confidence: 99%
“…The above deduces the attack cost in theory, we next verify our argument through performing a set of experiments using popular trust metrics: BetaTrust [Jøsang and Ismail 2002], EigenTrust [Kamvar et al 2003], ServiceTrust [Su et al 2013] and ServiceTrust ++ [Su et al 2015]. To fairly evaluate the attack cost, we set same experiment environment as reported in EigenTrust [Kamvar et al 2003], i.e., the experiment platform includes 60 good participants and 40 mischievous participants.…”
Section: A Ack Behavior Analysis and Evaluationmentioning
confidence: 74%
“…The heritage EigenTrust ++ [Fan et al 2012] and GroupTrust [Fan et al 2017], both employed this kind of binary rating. Differently, ServiceTrust [Su et al 2013] and ServiceTrust ++ [Su et al 2015] utilized the multiscale rating {-1, 0, 1, 2, 3, 4, 5} indicating bad, no-rating, neutral, fair, good, very good and excellent query transaction respectively.…”
Section: Direct Trust With Local Trust Aggregationmentioning
confidence: 99%
See 2 more Smart Citations